Propaganda and Da’wah in Digital Era (A Case of Hoax Cyber-Bullying Against Ulama) - Karim, Abdul; Wajdi, Firdaus (KARSA: Journal of Social and Islamic Culture, 2019)
The presence of the media with all conveniences has surrounded the lives of Muslims. The patterns and models of da’wah developed by the da'i should adjust to the era of information and communication technology. However, under the pretext of freedom, many media appearances tend to damage social values and order. The purpose of this study is to analysis the elements of propaganda and da’wah in the movement of cyber-bullying of scholars through the hoax which based on the existence of problems in Islamic da’wah done with contradictive, and online media utilized with provocative. The type of research used is descriptive qualitative research which is using documentation and direct observation by accessing the website then the data collected is analyzed by filling system analysis. The data source was obtained from an online web that broadcasted the news with the keywords da’wah, bullying ulama and hoaxes. The result of research indicates that element of da’wah only exist in cyber-bullying while the hoax more prominent in propaganda side. The data found are (1) the existence of ulama propaganda movements which are bullied; (2) propagation of ulama through hoaxes; and (3) the existence of perpetrators of cyber-bullying ulama movements; however (4) there are several parties responsible for overcoming cyber-bullying through hoax.